Development in Turbulent Times The Many Faces of Inequality Within Europe - Dobrescu, Paul (Springer International Publishing : Imprint: Springer, 2019)
This open access book explores the most recent trends in the EU in terms of development, progress, and performance. Ten years after the 2008 economic crisis, and amidst a digital revolution that is intensifying the development race, the European Union, and especially Central and Eastern Europe, are ardently searching for their development priorities. Against this background, by relying on a cross-national perspective, the authors reflect upon the developmental challenges of the moment, such as sustainable development, reducing inequality, ensuring social cohesion, and driving the digital revolution. They particularly focus on the relation between the less-developed Eastern part of the EU and its more developed Western counterpart, and discuss the consequences of this development gap in detail. Lastly, the book presents a range of case studies from different areas of governance, such as economy and commerce, health services, education, migration andpublic opinion in order to investigate the trends most likely to impact the European Union's medium and long-term development.